Numerical study on flow separation and force evolution in liquid nitrogen cavitating flow - Liu, Yi; Zhang, JinLing; Sun, Lilong; An, LiLi; Wang, XunMing; Cai, Jie; Zhang, Wei; Chen, Feng (Frontiers in Energy Research, 2023)
In this paper, a two-phase flow model and the improved thermal cavitation model are used to study the flow characteristics and the evolution of vorticity force for liquid nitrogen cavitation flow. The results are validated against the experimental data from NASA, which shows that the flow re-attachment occurs in the area where the boundary vorticity flux begins to decrease from its positive value. Alternatively, the flow separation occurs near the area with low boundary vorticity fluxes. Besides, the boundary vorticity flux changes typically from negative to positive around the cavity. The development of the cavity affects the surrounding vortex structure, which leads to the evolution of vorticity force and the fluctuations of lateral force and drag force. The results show that the drag force is magnified by the cavitation, and it first decreases and then increases in a typical cycle of cavity evolution. The negative resistance unit is mainly produced in the front of the cavity, and the positive resistance unit is also made in the rear of the cavity. When the attached cavity is shed, the positive drag elements decrease, and the drag force drops to its minimum. When the attached cavity is growing, the positive resistance elements behind the cavity increase, making the resistance force gradually increase. For the lateral force, the existence of the cavity produces lift elements pointing out of the surface outside the cavity, and the unsymmetrical distribution of the cavity leads to the fluctuation of the lateral force.